Learning to Forget: A Critical Review of Knowledge Management and Knowledge Exchange Initiatives in the Detective Service - Mofokeng, Jacob Tseko (International Journal of Criminology and Sociology, 2022)
KM and KE have recently become commonly used terms in law enforcement agencies. However, implementing KM initiatives successfully in the SAPS still poses a challenge. This paper reviews factors that influence the success or failure of KM and KE initiatives as manifested in the SAPS, with emphasis on the DS. Both KM and KE initiatives are of critical importance to solve criminal cases. The consulted literature review highlighted various dimensions that are critically influential in the implementation of KM and KE in the DS. These are the negligence of the FP, during which the building blocks for a successful schooling career are laid; and once detectives are recruited, the lack of a mentorship programme and training curriculum, which lack coherence, connection, as well as depth of understanding that accompanies systematic critical thinking.